تحديد الكادميوم في بعض المواد الغذائية المعروضة في كل من مدينة اللاذقية وحمص وطرطوس - الحكيم, قصي (Latakia University Journal -Biological Sciences Series, 2019)
ركزت هذه الدراسة على تقدير مستويات الكادميوم في بعض عينات المأكولات الساخنة الجاهزة والمأكولات الشعبية والخضار والفاكهة وبعض التوابل والأعشاب المجففة التي جمعت من دكاكين الأسواق المحلية في كلّ من مدينة اللاذقية وحمص وطرطوس، وقد تمّ التحليل باستخدام مطياف الامتصاص الذري (AAS). أظهرت النتائج أن تركيز الكادميوم في عينات بعض المأكولات الشعبية مثل الخبز والبرغل والأرز والثمار والبطاطا المقلية كانت طبيعية. ومن ناحية أخرى فإنّ مستويات الكادميوم في أغلب العينات المدروسة كانت أقل من الحدود المسموح بها والمقرّة من قبل الجهات المختصة , إذ تراوحت كميات الكادميوم في معظم الخضار بين 1.5 و77 جزء في البليون ppb , وفي البقدونس بين 33 و162 ppb , وفي المأكولات الساخنة الجاهزة بين 15 و 180.3 ppb . ولقد تمت مقارنة هذه المستويات بأخرى للأغذية نفسها في بقاع أخرى من العالم، وتبين أن مستويات الكادميوم في العينات المدروسة هي عموماً أدنى من المستويات المسموح بها المقرة من الهيئات الدولية. This study focused on estimating the levels of Cadmium in samples of snack foods, popular foods, vegetables, fruits, dried herbs and condiments. The samples were collected from available foodstuffs at local markets in Lattakia, Homs and Tartous. Cadmium was determined by Atomic Absorption Spectrometry (AAS). The results showed that Cadmium concentration in the samples of some local popular foods such as bread, split parboiled wheat, rice, fruits and fried potatoes was normal. On the other hand, Cadmium levels found in most samples were below the acceptable levels established by the regulatory organizations. Cadmium amounts detected in most vegetables ranged from 1.5 to 77ppb.and in parsley from 33 to 162 ppb, and in snack foods from 15 to 180.3 ppb. The levels compare well with those reported for similar foodstuffs from some other parts of the world. Overall, the present study showed that the levels of Cadmium are generally lower than the permissible levels.